Dampak Pajak Penghasilan Terhadap Kinerja Keuangan Perusahaan Di Indonesia - Wiena Tentunata Tentunata; Jesslyn MC Clane; Karlyn Clarissa Liong; Carlyn (Jurnal Riset Bisnis dan Ekonomi Digital, 2025)
This study aims to analyze the impact of the Corporate Income Tax (PPh Badan) rate change policy on the financial performance of companies in Indonesia. Using the Systematic Literature Review (SLR) approach, this study examines various empirical studies and relevant scientific journals from 2021 to 2025. The results of the analysis show that the reduction in the PPh Badan rate has a significant positive effect on the profitability, capital structure, and liquidity of companies. However, this effect varies depending on the business sector and company management strategy. In addition, this study found that companies utilize tax policy as part of an efficiency strategy and communication with investors, in accordance with agency and signaling theories. These findings provide important implications for policy makers in designing adaptive tax policies and for companies in managing financial and tax strategies to improve financial performance sustainably.